Effect of shear thickening gel on microstructure and impact resistance of ethylene–vinyl acetate foam. (1st May 2023) - Tu, Huan; Xu, Pengzhao; Yang, Zhe; Tang, Fan; Dong, Cheng; Chen, Yuchao; Cao, Wenjian; Huang, Chenguang; Guo, Yacong; Wei, Yanpeng
Abstract: To satisfy the ever-increasing demand for better anti-impact performance of personal protective equipment, a composite foam by incorporating shear thickening gel (STG) with ethylene–vinyl acetate (EVA) was developed. The superiorities of EVA foam in softness, lightness and flexibility were maintained in the novel material. The microstructure of STG/EVA composite foam was characterized using Scanning Electron Microscope. A series of experimental approaches including Dynamic Mechanical Analysis test, compression test, Split Hopkinson Pressure Bar test and drop hammer test were applied to study the material properties at different strain rates. Attributed to the shear thickening property of STG, STG/EVA exhibited significant strain rate sensitivity. The results showed that STG/EVA foam possessed better mechanical performance than plain EVA foam. In the ballistic test, the body armor consisting of the STG/EVA buffer layer possessed better protective performance than the regular one. The improvement mechanism was interpreted with micromorphological changes before and after tests. The introduced STG reinforced the integrity and continuity of microstructure to enhance the capability of the composite material in absorbing and dissipating impact energy. Therefore, the application prospect of the developed STG/EVA foam in personal protective equipment is promising.